Development of suction measurement techniques to quantify the water retention behaviour of GCLs. Issue 5 (1st October 2010) - Beddoe, R.A.; Rowe, R.K.; Take, W.A.
Abstract : ABSTRACT: Geosynthetic clay liners (GCLs) have the potential to act as excellent hydraulic barriers, and have been successfully used in numerous barrier system applications, including composite landfill liners. In order to function effectively in the role of a hydraulic barrier, these products must first hydrate through the uptake of moisture from the subsoil. They then must demonstrate adequate dimensional stability during any subsequent moisture loss, to avoid separation of the panel overlaps. The key to understanding these moisture uptake and retention phenomena is the constitutive relationship between suction and moisture content. This relationship is commonly referred to as the water retention curve (WRC) of a material. Despite the significance of this relationship for the final success of the barrier, only a few studies have successfully quantified portions of water retention curves, and for only a subset of available GCL product types. This scarcity of data is due primarily to the inherent difficulty of determining this function experimentally for a composite material such as a GCL, and to the difficulty in measuring the wide range of suctions that need to be investigated. In response to this data gap, a dual-technique strategy for the quantification of WRC for GCLs is investigated in this paper, in which two different suction measurement techniques (high-capacity tensiometers and capacitive relative humidity sensors) have been assessed to see whether they are capable of experimentally quantifying the relationship between moisture content and suction for a GCL. This paper discusses the sample preparation techniques and required equilibration times for these techniques, and demonstrates that they can provide water retention data for GCLs that are consistent with published results.